2009
DOI: 10.1111/j.1365-4632.2007.03291.x
|View full text |Cite
|
Sign up to set email alerts
|

Ichthyosis hystrix Curth–Macklin type in an African girl

Abstract: Ichthyosis hystrix Curth-Macklin type is a rare autosomal dominant skin disorder characterized by extensive hyperkeratosis and palmo-plantar keratoderma. It results from heterozygous frameshift mutation in keratin 1 gene (KRT1). Histological features, showing perinuclear vacuolization and binucleated cells, are similar to those of epidermolytic hyperkeratosis except for the absence of epidermolysis. The present report describes the condition in a 16-year-old African girl where available treatment was disappoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 8 publications
0
10
0
1
Order By: Relevance
“…IHCM is an autosomal dominant disorder that is characterized by palmoplantar keratoderma and hyperkeratotic, ridged or cobblestoned plaques over the large joints. 2 In this case, there was no specific histopathological change, for example, perinuclear halo or binucleated cells, 3 and no palmoplantar keratoderma was observed.…”
Section: Case Of Unilateral Epidermal Nevi Without Extracutaneous Anomentioning
confidence: 66%
“…IHCM is an autosomal dominant disorder that is characterized by palmoplantar keratoderma and hyperkeratotic, ridged or cobblestoned plaques over the large joints. 2 In this case, there was no specific histopathological change, for example, perinuclear halo or binucleated cells, 3 and no palmoplantar keratoderma was observed.…”
Section: Case Of Unilateral Epidermal Nevi Without Extracutaneous Anomentioning
confidence: 66%
“…Although sporadic cases have been reported in the literature (Mehta et al, 2015, Yusuf et al, 2009, Brusasco et al, 1994), IHCM is typically described using Ollendorff-Curth’s original description (Ollendorff-Curth et al, 1972) as an autosomal dominant condition recurring in two families (Niemi et al, 1990, Sprecher et al, 2001). More recent genetic linkage studies have revealed that various mutations in the KRT1 gene, which encodes keratin 1, play a central role in disease pathogenesis (Fonseca et al, 2013, Ishida-Yamamoto et al, 2003, Kubo et al, 2011, Richardson et al, 2006, Sprecher et al, 2001).…”
Section: Ichthyosis Hystrix Curth-macklin Typementioning
confidence: 99%
“…Ichthyosis hystrix of Curth and Macklin type is a rare autosomal dominant disorder with very few sporadic cases[3] reported since its first description in 1954. It is characterized by extensive, spiky, or verrucous, hyperkeratotic, ridged, or cobblestoned plaques over the large joints, hyperkeratotic papules on the trunk and extremities, with massive palmoplantar keratoderma leading to deep, bleeding, and painful fissures.…”
mentioning
confidence: 99%